2008
DOI: 10.1128/mcb.01661-07
|View full text |Cite
|
Sign up to set email alerts
|

Activated Kras, but Not Hras or Nras, May Initiate Tumors of Endodermal Origin via Stem Cell Expansion

Abstract: The three closely related human Ras genes, Hras, Nras, and Kras, are all widely expressed, engage a common set of downstream effectors, and can each exhibit oncogenic activity. However, the vast majority of activating Ras mutations in human tumors involve Kras. Moreover, Kras mutations are most frequently seen in tumors of endodermally derived tissues (lung, pancreas, and colon), suggesting that activated Kras may affect an endodermal progenitor to initiate oncogenesis. Using a culture model of retinoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 95 publications
1
94
1
2
Order By: Relevance
“…Consistent with this idea, a recent study revealed that the hypervariable domains of oncogenic K-Ras and H-Ras regulate self-renewal versus differentiation fates in the F9 mouse embryonal stem cell model. 39 Experimental data support the idea that AML is frequently initiated by a transcription factor fusion (class 1 mutation) but also requires a cooperating class 2 mutation that deregulates cellular signaling networks. 40 Consistent with this idea, some AML specimens contain subclones with independent RAS mutations, and RAS mutations that are detected at diagnosis may disappear over time.…”
Section: Nras G12d In Hematopoiesis and Leukemogenesis 2029mentioning
confidence: 71%
“…Consistent with this idea, a recent study revealed that the hypervariable domains of oncogenic K-Ras and H-Ras regulate self-renewal versus differentiation fates in the F9 mouse embryonal stem cell model. 39 Experimental data support the idea that AML is frequently initiated by a transcription factor fusion (class 1 mutation) but also requires a cooperating class 2 mutation that deregulates cellular signaling networks. 40 Consistent with this idea, some AML specimens contain subclones with independent RAS mutations, and RAS mutations that are detected at diagnosis may disappear over time.…”
Section: Nras G12d In Hematopoiesis and Leukemogenesis 2029mentioning
confidence: 71%
“…For example the preponderance of Kras mutations in human cancers correlated with the exclusive ability of constitutively active Kras to promote the proliferation of endodermal stem/progenitor cells and to block their differentiation, unlike constitutively active Hras that induce differentiation of these cells. 16 Even in this clear experimental setting, linking these phenotypical differences to distinct output of downstream signals was not possible. 16 Furthermore it was reported that each Ras Raf, it was shown that B-Raf activates MEK1/2 more efficiently than C-Raf (10-fold less) and A-Raf (500-fold less than B-Raf ).…”
Section: Do Isoforms Of the Ras/raf/mek/erk Pathway Gather To Constitmentioning
confidence: 99%
“…16 Even in this clear experimental setting, linking these phenotypical differences to distinct output of downstream signals was not possible. 16 Furthermore it was reported that each Ras Raf, it was shown that B-Raf activates MEK1/2 more efficiently than C-Raf (10-fold less) and A-Raf (500-fold less than B-Raf ). 27 However, these constructs only contain the Raf kinase domains and thus do not permit to assess any contributions by the regulatory Raf domains.…”
Section: Do Isoforms Of the Ras/raf/mek/erk Pathway Gather To Constitmentioning
confidence: 99%
“…Genetic alterations in the KRAS signaling pathway are involved in over 90% of pancreatic cancer cases (4)(5)(6). KRAS mutations were shown to be an early event in the development of pancreatic cancer (5,7,8).The most common KRAS mutation of the human pancreas adenocarcinoma is a gain-of-function substitution mutation of glycine at codon 12 to aspartate (G12D) (5,(9)(10)(11). Moreover, PDA cancer cell growth was shown to be dependent on the activity of the mutated KRAS (5,11) and accordingly, silencing KRAS has proven effective in controlling pancreatic cell line proliferation (12).…”
mentioning
confidence: 99%